Transmedia Narratives Applied by Communication Students in the Dissemination of Cultural Heritage - Quezada-Tello, Laddy-Liset; Hernando-Gómez, Ángel; Vázquez-Aguado, Octavio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The evolution of technology has influenced the media ecology, making transmedia to be applied in fictional, journalistic, educational narratives, etc. This research analyzes the experimental production process in the project Orotopia, developed by students of Social Communication of the Technical University of Machala- UTMACH, Ecuador. Results show that its non-formal application becomes an option for learning about cultural heritage; it also allows going through the collaborative production process of students to produce audiovisual reports, podcasts, radio programs, and content for social networks.